2013
DOI: 10.1080/14763141.2013.769619
|View full text |Cite
|
Sign up to set email alerts
|

Stiffness, intralimb coordination, and joint modulation during a continuous vertical jump test

Abstract: This study analysed the modulation of jump performance, vertical stiffness as well as joint and intralimb coordination throughout a 30-s vertical jump test. Twenty male athletes performed the test on a force plate while undergoing kinematic analysis. Jump height, power output, ground contact time, vertical stiffness, maximum knee and hip flexion angles, and coordination by continuous relative phase (CRP) were analysed. Analysis of variance was used to compare variables within deciles, and t-tests were used to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 30 publications
1
19
1
Order By: Relevance
“…This fact could be explained by differences in the exercises used and the electrical parameters applied in both intervention groups (e.g., the inclusion of several plyometric exercises in the PFG). Since the main difference between CMJ and ABJ is the contribution of interlimb coordination, the improvement obtained in ABJ in the PFG when compared to the TG, suggest that a periodized and functional WB-EMS training program could have a considerable impact on inter-limb coordination (Dal Pupo et al, 2013 ). However, more studies are needed to elucidate which physiological or biomechanical mechanism may explain the differences reported between groups.…”
Section: Discussionmentioning
confidence: 99%
“…This fact could be explained by differences in the exercises used and the electrical parameters applied in both intervention groups (e.g., the inclusion of several plyometric exercises in the PFG). Since the main difference between CMJ and ABJ is the contribution of interlimb coordination, the improvement obtained in ABJ in the PFG when compared to the TG, suggest that a periodized and functional WB-EMS training program could have a considerable impact on inter-limb coordination (Dal Pupo et al, 2013 ). However, more studies are needed to elucidate which physiological or biomechanical mechanism may explain the differences reported between groups.…”
Section: Discussionmentioning
confidence: 99%
“…Kinetic and kinematic changes in jumping performance have been observed with various loads and amounts of fatigue. [1][2][3][4] Research has shown that adding a load of 20 kg was enough to statistically alter the force, velocity, power and displacement in untrained individual's squat jump performance. 1 The previously mentioned sample had a mean body mass of 80.8 kg, therefore the 20 kg load represented an additional mass of 24.75%, causing decrements of 13.69% in peak power and 22.22% in jump height.…”
Section: Introductionmentioning
confidence: 99%
“…Fatigue may be accompanied by decreases in jump height, flight time, eccentric force production, power, vertical stiffness, and knee flexion angles. [4][5][6] Fatigue has also been associated with increases in ground contact time and with decreases in angular velocities and accelerations in jumps. 4,[6][7] Furthermore, fatigue has been associated with knee joint stability decreases, that may increase the risk of injury in both males and females.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…11 Similarly, alterations in bat position throughout a swing may be related to onset or accumulation of fatigue. But similar to bat swing velocity, more research is required to validate this speculation.…”
Section: Disscusionmentioning
confidence: 99%